Anomalous ferroelectricity in P(VDF70-TrFE30). Issue 1 (4th April 2017) - Mehner, Erik; Jachalke, Sven; Hanzig, Juliane; Leisegang, Tilmann; Stöcker, Hartmut; Meyer, Dirk C.
ABSTRACT: The ferroelectric phase transition of copolymers of vinylidene fluoride (VDF) with trifluoroethylene (TrFE) is well known and related to conformational changes in the polymer chain. Contrary to the expected paraelectric behaviour in the high temperature phase a pyroelectric investigation of the phase transition in the range from 0°C to 130°C combined with X-ray diffraction indicate the copolymer as ferroelectric when prepared and polarised in the high-temperature phase. Based on this finding the orthorhombic space-group Fmm 2 is proposed for the polar high-temperature phase. Above the Curie temperature the material exhibits pyroelectricity with inverted sign, whose origin is interpreted as flexoelectricity.